The development of food preferences: anatomical and genetic determinants, important factors of taste development in children - I.N. Zakharova; Yu.A. Dmitrieva; E.B. Machneva; A.N. Tsutsaeva (LCC «Medicine-Inform», 2020)
I.N. Zakharova1, Yu.A. Dmitrieva1, E.B. Machneva2, A.N. Tsutsaeva3 1Russian Medical Academy of Continuous Professional Education, Moscow, Russian Federation 2Russian Children's Clinical Hospital of the Pirogov Russian National Research Medical University, Moscow, Russian Federation 3Stavropol State Medical University, Stavropol, Russian Federation Since ancient times, scientists and philosophers were interested in the sense of taste, the mechanisms of its development, anatomical structures responsible for taste, and its importance. Currently, it is clear that food preferences are the main determinant of the development of nutrition and food behavior. Food preferences begin to develop in the early childhood and retain throughout the life. Therefore, inculcating correct nutritional behavior with respect to healthy food is a promising approach to improve the quality of diet being one of the key factors affecting human health. This article addresses current data on morphology, genetics, embryology, and ontogeny of gustatory system as well as major factors affecting the development of food preferences in a child. Most of these factors are modified ones, therefore, the aim of this review is to draw the attention of pediatricians since this is pediatrician who makes evidence-based recommendations on child nutrition and provide s adequate feeding strategy. Keywords: genetics, food preferences, taste, taste receptors, children, smell, ontogeny, tongue, baby food, healthy lifestyle. For citation: Zakharova I.N., Dmitrieva Yu.A., Machneva E.B., Tsutsaeva A.N. The development of food preferences: anatomical and genetic determinants, important factors of taste development in children. Russian Journal of Woman and Child Health. 2020;3(2):119-125. DOI: 10.32364/2618-8430-2020-3-2-119-125.